2010
DOI: 10.1039/c0cc00747a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of functionalized resorcinols by rhodium-catalyzed [5+1] cycloaddition reaction of 3-acyloxy-1,4-enynes with CO

Abstract: A novel [5+1] type carbonylative cycloaddition reaction has been developed using a Rh complex as catalyst. This reaction can convert readily available 3-acyloxy-1,4-enynes and CO to a wide range of functionalized resorcinols in good yields. A mechanism involving Rh-catalyzed cyclocarbonylation of 3-acyloxy-1,4-enynes accompanied by a 1,2-acyloxy shift is proposed for the present [5+1] type cycloaddition reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 36 publications
2
30
0
2
Order By: Relevance
“…23 ACE was recently also employed as a 5C synthon in a novel Rh(I)-catalyzed [5+1] cycloaddition with CO for the synthesis of highly substituted phenols. 24 …”
Section: Introductionmentioning
confidence: 99%
“…23 ACE was recently also employed as a 5C synthon in a novel Rh(I)-catalyzed [5+1] cycloaddition with CO for the synthesis of highly substituted phenols. 24 …”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that 3-acyloxy-1,4-enynes with a terminal alkyne can serve as a five-carbon building block for [5+1] [157] and [5+2] [158] cycloadditions with CO and alkynes, respectively. Moreover, both of these cycloadditions involve a rhodium-catalyzed 1,2-acyloxy migration of propargyl esters which was reported in 1984 [159,160].…”
Section: %mentioning
confidence: 99%
“…56, 65 This method provided access to various functionalized resorcinol derivatives from readily available 3-acyloxy-1,4-enynes.…”
Section: Cycloadditions Involving Rh-catalyzed 12-acyloxy Migratimentioning
confidence: 99%